microbiological and general appearance of fresh wonderful Punica granatum L. - Pretell, Carla (2016)
Evaluate the effect of gaseous ozone on physicochemical characteristics, molds and yeasts count and overall appearance of granada. Wonderful variety fruits of granada was collected in a glass chamber where the gas is injected using ozone generator equipment with flow of 500 mg / h and a digital meter for measuring the ozone concentration. A central composite design rotable (CCDR) was used to analyze the effect of the concentration of ozone gas and storage time (p < 0.05) on weight loss, firmness, shell color, soluble solids, mold and yeasts count, total anthocyanins content and overall appearance. It was determined that the concentration of ozone gas had significant effect on the responses studied variables. The quadratic model provided the best fit of data. It was established that the concentration of ozone between 40 - 50 ppm, it allows for the lowest weight loss, low count of molds and yeasts; greater firmness, soluble solids, shell color, total anthocyanins content and overall appearance in Granada during 50 - 55 days of storage.